Isolation and proteomic analysis of the SYP61 compartment reveal its role in exocytic trafficking in Arabidopsis - Drakakaki, Georgia; Keinath, Nana; Schumacher, Karin (Cell research, 2012)
The endomembrane system is a complex and dynamic intracellular trafficking network. It is very challenging to track individual vesicles and their cargos in real time; however, affinity purification allows vesicles to be isolated in their natural state so that their constituent proteins can be identified. Pioneering this approach in plants, we isolated the SYP61 trans-Golgi network compartment and carried out a comprehensive proteomic analysis of its contents with only minimal interference from other organelles. The proteome of SYP61 revealed the association of proteins of unknown function that have previously not been ascribed to this compartment. We identified a complete SYP61 SNARE complex, including regulatory proteins and validated the proteome data by showing that several of these proteins associated with SYP61 in planta. We further identified the SYP121-complex and cellulose synthases, suggesting that SYP61 plays a role in the exocytic trafficking and the transport of cell wall components to the plasma membrane. The presence of proteins of unknown function in the SYP61 proteome including ECHIDNA offers the opportunity to identify novel trafficking components and cargos. The affinity purification of plant vesicles in their natural state provides a basis for further analysis and dissection of complex endomembrane networks. The approach is widely applicable and can afford the study of several vesicle populations in plants, which can be compared with the SYP61 vesicle proteome.